Peranan Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru - Nuraisyah, Siti (Program Studi Akuntansi IKOPIN, 2022)
This study aims to describe the principal's leadership in improving teacher performance and the inhibiting factors of the principal's leadership in improving teacher performance. This research uses descriptive qualitative with case studies in a school environment. The subjects in this study were principals and teachers. Data collection techniques are observation, interviews, and document studies. The technique used is through data and data presentation and existing conclusions. The results of the study show that the Principal's Leadership in improving teacher performance is quite good in developing teacher performance, supervising teachers in working on lesson plans, syllabus, Prota, Prosem, KKM, and evaluating in improving teacher quality. There are also supporting factors with good support and motivation. from the Principal. Which can improve the quality of teachers in teaching in schools. There are also inhibiting factors such as an unstable network, the ability of teachers who do not master the class, learning methods that are not suitable, the discipline factor of teachers coming to school. Based on this research, the principal must affirm the teacher to the maximum to create a school that is by government policies.